Buletin Peternakan : Pengaruh Pakan Tambahan Berupa Ampas Tahu Dan Limbah Bioetanol Berbahan Singkong (Manihot utilissima) Terhadap Penampilan Sapi Bali (Bos sondaicus) - dwi dedeh kurnia sari (Peternakan UGM, 2016)
This study was aimed to observe the performance of Bali cattle given additional feed of tofu waste, solid and liquid waste of bio-ethanol made from cassava. Six male Bali cattle with body weight of 190- 230 kg were used. The design of this study was a 3x3 Latinsquare with cross over pattern.